Pengembangan Website Profile Pada Pondok Pesantren Pelajar Mahasiswa Nurul Islam Samarinda - Willy Wildan Solikhan; Haeruddin; Eko Subastian (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2026)
This research was motivated by the limited information media at Pondok Pesantren Pelajar Mahasiswa (PPPM) Nurul Islam Samarinda, which still relied on traditional methods such as brochures and banners. As a result, information dissemination was inefficient and less accessible to the wider community. Therefore, the development of a profile website was carried out as an official information medium to improve transparency, accessibility, and the pesantren’s public image in the digital era. This study employed a Research and Development (R&D) approach using the Waterfall model, which includes the stages of analysis, design, implementation, testing, and maintenance. The product developed is a profile website built using the Laravel framework, supported by MySQL, HTML, CSS, and JavaScript. The website provides information on the history, vision and mission, programs, facilities, achievements, galleries, and learning materials of the students, and is equipped with a Content Management System (CMS) for data management. The feasibility test by media experts showed a score of 95.8%, categorized as very feasible. Meanwhile, the user trials involving teachers, students, and the community obtained an average SUS score of 96.4, categorized as acceptable, indicating that the website was well received. These results demonstrate that the website meets not only functional aspects but also usability in terms of user convenience and satisfaction. In conclusion, the PPPM NURIS profile website was successfully developed, meeting institutional needs and serving as a medium for communication, promotion, documentation, and institutional branding in the wider community. It is suggested that the pesantren administrators carry out regular maintenance and add interactive features such as online registration and e-learning to ensure the sustainability of the system